ANALISIS MANAJEMEN PROGRAM TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN TAHFIDZUL QUR'AN : STUDI LITERATUR - ahmad_fauzan; Oki Dermawan (STIT Bustanul 'Ulum Lampung Tengah, 2025)
Islamic boarding schools (pesantren) have long played a significant role in producing generations of Qur’an memorizers (huffaz). However, the effectiveness of tahfidz programs greatly depends on how well these are managed. This study aims to analyze the management of tahfidz programs in pesantren based on a comprehensive literature review. The research focuses on three core areas: planning, implementation, and evaluation, which are essential pillars in managing religious education programs. Using a qualitative-descriptive approach with content analysis of recent studies (within the last 10 years), the findings reveal that effective planning includes personalized curriculum design and strategic scheduling. Implementation requires competent teachers, varied memorization methods (such as talaqqi, muroja’ah, and digital tools), and a conducive learning environment. Evaluation is most effective when supported by structured feedback systems, parent involvement, and the integration of technology, including AI-based assessment tools. The study concludes that the integration of traditional religious values with modern management practices and digital innovations significantly enhances the success of tahfidz programs. It also recommends a personalized, data-driven management model to increase memorization retention and support the long-term sustainability of tahfidz education. These findings offer strategic insights for pesantren leaders, Islamic educators, and policy makers to develop more adaptive and effective tahfidz systems.